The prediction of wake wash in the towing tank - Abdul Ghani, Mohamad Pauzi (Faculty of Mechanical Engineering, 2008)

(untitled)
The wash or ship-generated waves from high speed craft has become a common subject in research and development of marine transportation. Since some time now the wake wash of high speed craft has become a problem in particular on inland or confined waterways. This wake wash has an impact on safety and environment such as bank/shoreline erosion, risk to people on shore and small boats in harbors and changes in the local ecology. This paper describes the results of model test of a high speed patrol, together with theoretical prediction of wake wash.